2018
DOI: 10.18203/2320-6012.ijrms20184062
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of propofol and etomidate as anaesthetic agents for elective non-cardiac surgery

Abstract: Background: To compare propofol and etomidate as anaesthetic agents for elective non-cardiac surgery with respect to stability of haemodynamic parameters, systemic side effects and quality of induction.Methods: Randomised, blinded study of 100 patients posted for elective non-cardia surgery under general anaesthesia, divided in to two group. In group P(n=50) induction was achieved with injection Propofol 1mg/kg, whereas in group E(n=50), it was achieved with injection etomidate 0.3mg/kg after premedication wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Our finding is also similar to the finding of Kumar A et al studies on propofol and etomidate as anaesthetic agent for elective non cardiac surgery where they found that there was no statistically significant difference in two group regarding nausea and vomiting. 28…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is also similar to the finding of Kumar A et al studies on propofol and etomidate as anaesthetic agent for elective non cardiac surgery where they found that there was no statistically significant difference in two group regarding nausea and vomiting. 28…”
Section: Discussionmentioning
confidence: 99%
“…Jing Wu et al 14 , also observed that Etomidate is much safer than Propofol for first-trimester surgical abortions and using a lower dose of Etomidate, supplemented with Fentanyl and Midazolam, in reducing adverse effects like myoclonus and postoperative nausea and vomiting. Amit Kumar et al in 2018 15 also conducted a similar study for elective non-cardiac surgery to compare Propofol and Etomidate as anaesthetic agents and found that Etomidate is a better intravenous induction agent of anaesthesia than Propofol in hemodynamically unstable patient also as it has faster onset of action with less pain and post-operative nausea, vomiting with good hemodynamic stability. The SpO 2 in both the groups was maintained at 100% throughout the surgery and also in the post op period.ECG monitoring was done in both the groups throughout the procedure.…”
Section: Discussionmentioning
confidence: 99%